1979
DOI: 10.21236/ada078234
|View full text |Cite
|
Sign up to set email alerts
|

Failure Causing Defects in Ceramics: What NDE Should Find

Abstract: The various types of defects causing failure in a variety of ceramic materials are illustrated. Examples are drawn from such ceramics as piezoelectric, infrared transmitting, and potential turbine materials. Both machining and processing defects are shown as sources of failure. The former are selected to illustrate the effects of machining parameters. Processing defects illustrated include pores, foreign particles and large grains, or clusters of these. Changes in the size of defects with specimen size are als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1983
1983
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Minor compositional inhomogeneities, such as larger crystallites or clusters present on the surface of pellets may have contributed to the formation of surface defects, by providing preferential locations for flaws upon pressure-heat-treatment when preparing the MOF-CGCs. [26] The glass (a g ZIF-62) 1.0 pellet however, was comparatively free of surface defects (Figure 4f), highlighting the high quality of pellet produced from melt-quenched samples of ZIF-62(Zn) glass. Despite the presence of surface defects, single-component MOF-CGC samples showed no evidence of individual ZIF-62(Zn) crystallites on the surface, suggesting good interfacial compatibility between the crystalline and glass-phases.…”
Section: Surface Propertiesmentioning
confidence: 97%
“…Minor compositional inhomogeneities, such as larger crystallites or clusters present on the surface of pellets may have contributed to the formation of surface defects, by providing preferential locations for flaws upon pressure-heat-treatment when preparing the MOF-CGCs. [26] The glass (a g ZIF-62) 1.0 pellet however, was comparatively free of surface defects (Figure 4f), highlighting the high quality of pellet produced from melt-quenched samples of ZIF-62(Zn) glass. Despite the presence of surface defects, single-component MOF-CGC samples showed no evidence of individual ZIF-62(Zn) crystallites on the surface, suggesting good interfacial compatibility between the crystalline and glass-phases.…”
Section: Surface Propertiesmentioning
confidence: 97%
“…If this is indeed the case, it must concluded that the higher measured values are related to the pore size and distribution evident in the specimens with the larger grain size. For specimens with equivalent bulk density this would have to be accounted for by the value assigned to the porosity correction factor b in equation (2).…”
Section: Microstructuresmentioning
confidence: 99%
“…For ceramic implants, the surface, in addition, strongly affects the mechanical strength and wear resistance. Based on their inherent brittle nature, the strength of ceramics is highly sensitive to the existence of surface flaws (cracks, pores, scratches) and even in their absence failure may occur initiated from the microscopic roughness of large grains [ 11 , 12 ]. For that reason, commercial full-ceramic ZrO 2 or Al 2 O 3 artificial hip and knee implants are typically polished (R a < 10 nm) to avoid surface defects and to achieve a high strength and a low-friction surface [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%